2′‐Fucosyllactose promotes Lactobacillus rhamnosus KLDS 8001 to repair LPS‐induced damage in Caco‐2 cells. Issue 5 (3rd February 2022) - Li, Aili; Zhang, Chao; Chi, Houyu; Han, Xueting; Ma, Yiming; Zheng, Jie; Liu, Chuan; Li, Chun
Abstract: The aim of this study was to investigate the effect of 2'‐fucosyllactose (2′‐FL) on the repair of monolayer barrier damage in Caco‐2 cells by Lactobacillus rhamnosus KLDS 8001 (KLDS 8001). The results showed that the addition of 2′‐FL not only promoted the adhesion ability of KLDS 8001 to Caco‐2 cells but also improved the anti‐adhesive effect of pathogenic bacteria. Compared with 2′‐FL or KLDS 8001 alone, 2′‐FL+KLDS 8001 significantly reduced lipopolysaccharide (LPS)‐induced malondialdehyde (MDA), lactate dehydrogenase (LDH) release, and cytokine (IL‐1β, IL‐6, and TNF‐α) production. In addition, 2′‐FL effectively promoted the transmembrane electrical resistance (TEER), cell viability, and cellular permeability of KLDS 8001 repaired damaged cells with dose‐dependent properties. The mRNA and protein expression of Zonula Occludens‐1 (ZO‐1), Occludin, and Claudin‐1 were also upregulated in the KLDS 8001 and 2′‐FL co‐treated treatment group. It was speculated that 2′‐FL could effectively regulate the interaction between KLDS 8001 and intestinal epithelial cells to play a role in maintaining intestinal barrier function and avoiding pathogenic bacteria invasion. Practical applications: As the most widely used human milk oligosaccharides (HMOs), 2′‐FL is vital for maintaining infant intestinal health. Our study found that the addition of 2′‐FL promoted KLDS 8001 adhesion, anti‐adhesion of pathogenic bacteria, anti‐inflammatory capacity, repair of barrier damage, and tight junction protein expression, providing a new strategy to protect infant intestinal health and prevent various intestinal diseases. Abstract : 2′‐FL promoted the repair of LPS‐induced monolayer barrier damage in Caco‐2 cells by KLDS 8001, especially the addition of 2′‐FL (400 μg/mL) was most effective. In addition, the mRNA and protein expression of ZO‐1, Occludin, and Claudin‐1 were up‐regulated in the combined group of 2′‐FL and KLDS 8001, indicating that 2′‐FL promoted the repair of LPS‐induced cell damage by KLDS 8001 was closely related to the expression of tight junction genes.